2023
DOI: 10.1007/s00415-023-11615-3
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa–carbidopa intestinal gel in advanced Parkinson’s disease: long-term results from COSMOS

Abstract: Background While immediate benefits of levodopa–carbidopa intestinal gel (LCIG) are evident in patients with Parkinson’s disease (PD), long-term LCIG effects require further study. Objectives We explored long-term LCIG on motor symptoms, nonmotor symptoms (NMS), and LCIG treatment settings in patients with advanced PD (APD). Methods Data were obtained (medical records and patient visit) from COSMOS, a multinational,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Clinical benefit for more than 15 years is documented in some patients for DBS 19 and for more than 5 years for LCIG. 43 CSAI, although being clinically effective for more than 3 years, is often used as a bridging therapy because of its less-invasive procedures 10 and is characterized by a relevant dropout in studies because of side effects (mainly neuropsychiatric and cutaneous), 10,41 thereby resulting in the shortest time of use of all 3 ATs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical benefit for more than 15 years is documented in some patients for DBS 19 and for more than 5 years for LCIG. 43 CSAI, although being clinically effective for more than 3 years, is often used as a bridging therapy because of its less-invasive procedures 10 and is characterized by a relevant dropout in studies because of side effects (mainly neuropsychiatric and cutaneous), 10,41 thereby resulting in the shortest time of use of all 3 ATs.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical benefit for more than 15 years is documented in some patients for DBS 19 and for more than 5 years for LCIG. 43 CSAI, although being clinically effective for more than 3 years, is often used as a bridging therapy because of its less-invasive procedures 10 and is characterized by a relevant dropout in studies because of side effects (mainly neuropsychiatric and cutaneous), 10,41 44 Cost reduction efforts need to be discussed for AT combinations because an addition of costs in AT combinations is expected (devices, surgery, hospitalization, and continuous drug provision). No data so far exist concerning real-life costs of combined ATs, compared with best medical treatment, however.…”
Section: Discussionmentioning
confidence: 99%
“…DUOGLOBE demonstrated that benefits with respect to off time and other parameters persist for at least 3 years [4 ▪ ]. COSMOS reported continued efficacy in patients treated for 5 years or more [14]. A recent report from Canada described patients treated for 5 years or more, with persistent improvement in off time (mean 3.3 h) and no worsening of dyskinesia [15].…”
Section: Levodopa-carbidopa Intestinal Gelmentioning
confidence: 99%
“…Currently, surgical methods available for the treatment of PD include deep brain stimulation (DBS) [ 10 , 11 ], levodopa carbidopa intestinal gel therapy [ 12 ], HIFU ablation of the subthalamic nucleus [ 13 ], and other methods, but these methods are highly invasive. At present, HIFU is mainly used clinically for PD, such as MRgFUS (unilateral [ 14–16 ] or bilateral [ 17 , 18 ]), and unilateral FUS-STN [ 19 ].The clinical efficacy of non-incisional transcranial MRgFUS will ultimately rest in appropriate target selection and optimized thermolesional coverage of the target [ 16 , 20 ].…”
Section: Clinical Application Of Fus In the Treatment Of Pdmentioning
confidence: 99%